(untitled) (Global Journal of Medical Research, 2020)
Parameter is causing the coronavirus (COVID-19) pandemic was CO 2 emissions, correlated with total cases (R 2 =0.8064) and deaths (R 2 =0.7627). CO 2 emissions produced by coal and gas-powered plants, oil refineries, vehicle, metropolitan food waste gas, human exhalation, leather-tannery industry, and organic dye industry. Cetaceans, including whales, dolphins, and porpoises, transmitted the globe with the coronavirus. The sudden spread of the coronavirus could cause by the 14 habitats of humpback whales, linked to millions of dolphins as well as the global leather tanning industry. It is necessary to monitor the sunspot number to prepare for the effects of cyclic minimum sunspot number in 2031. Because the top 2 countries of CO 2 emissions are China and the USA, a new pandemic in 2031 may initiate either from China or from the USA, as H1N1 (the USA, 2009) or as COVID-19 (China, 2020). The preventive phenomena of the third pandemic in 2031 can be monitored at humpback whale districts, as happened in 130 dead dolphins in Cape Verde, at least three months earlier before COVID-19 in China. UV-B radiation is the most efficient method to kill the virus itself.